Development and Evaluation of Levofloxacin-Based In situ Floating Gel for Enhanced Gastric Retention - Nale, Aniket Anand; Thorat, Priyanka Abaso; Mulla, Jameel Ahmed Sayed Gous (Indian Journal of Pharmaceutical Education and Research)
Background: This work focuses on the development and testing of a floating in situ gel system based on sodium alginate that delivers levofloxacin to treat stomach Helicobacter pylori infections. Materials and Methods: As the gelling and gas-forming ingredients, respectively, sodium alginate and calcium carbonate were added in different amounts to create nine distinct formulations. Drug content, pH, viscosity, in vitro gelation, floating behavior and in vitro drug release were all assessed for the produced gels. Results: Results demonstrated that the formulation F6, with an optimal balance of sodium alginate and calcium carbonate, exhibited desirable viscosity, prolonged floating time and sustained drug release over 24 hr. The in vitro gelation studies confirmed immediate gel formation and integrity maintenance in acidic conditions, ensuring effective drug retention and release in the gastric environment. The drug release kinetics followed a first-order model, indicating a controlled and predictable release profile. Conclusion: In conclusion, the sodium alginate-based floating in situ gel system presents a viable and efficient approach for the targeted delivery of levofloxacin, enhancing its therapeutic efficacy against H. pylori by prolonging gastric residence time and ensuring sustained drug release.
Keywords: Floating in situ gel; Levofloxacin; Helicobacter pylori; Gastro-retentive drug delivery; Sustained drug release.